Étudier les classes inversées en mathématiques. Préalables méthodologiques sur les cours : le cas particulier des « capsules » - Cécile Allard; Aline Robert (Recherches en Éducation)
In mathematics, in secondary and university education, some teachers can be considered as "inverters" in the sense of the five criteria retained in the presentation of the dossier, even if in this discipline there is a great diversity of inversion practices. To advance on the questioning of this type of device, which involves the exposure of knowledge differently from what is done in classical sessions, we make a methodological detour. In keeping with the theory of activity, we present specific ways of analyzing the moments of knowledge exposure, whatever the process, in class or not. From some studies carried out in didactics of mathematics on this subject, we draw out the first common results. A discussion on the advantages and disadvantages of the two types of knowledge exposure modalities, with or without inversion, concludes this work. This leads us to hypothesize about inversion and opens perspectives for further work.